2022
DOI: 10.3390/su141811650
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Tendency and Association Analysis of Intelligent Coal Mines in China: A Policy Text Mining Study

Xiaofang Wo,
Guichen Li,
Yuantian Sun
et al.

Abstract: The intellectualization of coal mines provides core technical support for the high-quality development of the coal industry. Intelligent texts, especially intelligent policy documents, play an extremely important role in analyzing the trend of intelligent policies in coal mines. This paper collects more than 50 central and local intelligent coal mine policy texts from recent years. The method of text analysis is a tool used for text mining, and semantic networks are generated; it reflects that the policy mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Hong et al found that the optimized scheduling of driverless electric trucks significantly reduces the total energy consumption during terminal operations, outperforming traditional diesel trucks and automated guided vehicles (AGVs) in terms of efficiency, economy, and social benefits [22]. Zhang et al presented a study on an obstacle avoidance planning method for driverless trackless rubber-tired vehicles (TRTV) in the confined spaces of deep wells [23]. However, nobody has redesigned the road widths for unmanned vehicles.…”
Section: Driverless Technologymentioning
confidence: 99%
“…Hong et al found that the optimized scheduling of driverless electric trucks significantly reduces the total energy consumption during terminal operations, outperforming traditional diesel trucks and automated guided vehicles (AGVs) in terms of efficiency, economy, and social benefits [22]. Zhang et al presented a study on an obstacle avoidance planning method for driverless trackless rubber-tired vehicles (TRTV) in the confined spaces of deep wells [23]. However, nobody has redesigned the road widths for unmanned vehicles.…”
Section: Driverless Technologymentioning
confidence: 99%
“…Coal mining is a crucial industry in China, with more than 90% of coal production occurring underground. Consequently, the use of underground mine cars is widespread, driven by various factors [1,2]. One significant advantage of underground mine cars is their ability to transport materials within mining sites.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous development of science and technology, domestic and foreign coal mining is developing towards a safe, green, low-carbon and efficient direction [1][2][3]. In recent years, the pace of intelligent development of coal mines in China has accelerated [4].…”
Section: Introductionmentioning
confidence: 99%